Hydrothermal alteration mapping of Siberian gold-ore fields based on satellite spectroscopy data - Ananyev, Yuri Sergeyevich; Maskov, A.A.; Abramova, Raisa Nikolaevna (IOP Publishing, 2015)
The mapping of the hydrothermal alterations in Urjahskoe and Fedorov-Kedrov gold-ore fields was conducted by applying channel relationship method (band ratio) based on ASTER spectral-zonal satellite image data. It was determined that the calculated mineral indices in ore-bearing structures are zonal. Outer ore-bearing structures revealed increased ferric mineral index values, while inner - high epidote- chlorite- calcite and muscovite- siderite mineral index values. Detected regularities could be used in identifying potential gold-ore bearing areas within identical fields based on remote sensing survey data.
Keywords: гидротермальные изменения; золоторудные месторождения; спутниковые данные; спектроскопия; рудоносные структуры; дистанционное зондирование